Evaluation of analgesic interaction between morphine, maropitant and dexmedetomidine in dogs undergoing ovariohysterectomy. Issue 1 (2nd January 2022) - Karna, SR; Chambers, P; Singh, P; Lopez-Villalobos, N; Kongara, K
ABSTRACT : Aims: To compare the analgesic effect of morphine combined with maropitant and/or dexmedetomidine to morphine alone but at a higher dose, and to evaluate the pharmacokinetics of the drug combinations, in dogs undergoing ovariohysterectomy (OHE). Methods: Forty client-owned dogs were randomised into four treatment groups (n = 10 per group) each to receive a different analgesic protocol. After premedication with I/M acepromazine, anaesthesia was induced with propofol to effect and maintained with isoflurane in 100% oxygen delivered via a circle system. The heart rate, respiratory rate, blood pressure, haemoglobin oxygen saturation, end-tidal partial pressure of carbon dioxide, electrocardiogram and rectal temperature were monitored during anaesthesia. The test drugs (Mor: 0.6 mg/kg morphine; Maro + Mor: 0.3 mg/kg morphine and 1 mg/kg maropitant; Dex + Mor: 0.3 mg/kg morphine and 10 μg/kg dexmedetomidine; Dex + Maro + Mor: 0.2 mg/kg morphine, 7 μg/kg dexmedetomidine and 0.7 mg/kg maropitant) were administered I/M after induction of anaesthesia and 30 minutes before the expected start time of ovariohysterectomy, which was carried out by veterinary students under veterinary supervision. The short form of the Glasgow composite measure pain scale (CMPS-SF) and visual analogue scale (VAS) were used for pain assessment at 15 and 30 minutes and 1, 2, 3, 6, 9 and 24 hours after extubation. Dogs with CMPS-SF pain score ≥ 6 received rescue analgesia with S/C buprenorphine (0.02 mg/kg). Blood samples were collected before, 15, 30, 60 and 120 minutes after injection of the test drugs and concentration of the test drugs in plasma was determined by liquid chromatography-mass spectrometry. Results: Dogs that received Dex + Mor had significantly lower CMPS-SF (estimate of difference = –1.53 (SE 0.58); p = 0.010) and VAS (estimate of difference = –0.67 (SE 0.25); p = 0.007) scores compared to the dogs that received morphine alone. There was no evidence of a difference in the number of dogs requiring rescue between groups. All dogs that received dexmedetomidine showed cardiac arrhythmia and second-degree heart block. Mean (SD) maximum concentrations (Cma x, ) of morphine in plasma were 6.8 (4.56), 9.56 (8.29), 9.30 (3.35) and 18.99 (9.41) ng/mL for the groups Dex + Mor, Dex + Maro + Mor, Maro + Mor and Mor respectively. The Cmax of morphine was significantly lower in the Dex + Mor (p = 0.004), Dex + Maro + Mor (p = 0.034) and Maro + Mor (p = 0.018) groups compared to the Mor group. Conclusions: For dogs undergoing ovariohysterectomy, lower doses of morphine (0.2 and 0.3 mg/kg) combined with dexmedetomidine or maropitant may provide analgesia equivalent to or better than morphine when given alone at a higher dose (0.6 mg/kg). Abbreviations: AUC: Area under curve; Cmax : Maximum concentration in plasma; CMPS-SF: Glasgow composite measure pain scale – short form; NK1: Neurokinin-1; OHE: Ovariohysterectomy; Tmax : Time to Cmax ; T1/2 : Half-life of terminal elimination phase; VAS: Visual analogue scale